Internet Addiction and Cyber Ethic Issues Among Students from Secondary School in Malaysia - Kristy Elity, Sulaiman; Tan, Choon Keong (2018)
This paper aims to examine the level of internet addiction and its relationship with cyber ethic issues among students from a secondary school located in a rural area in Malaysia. This paper focuses on identifying the level of internet addiction among students and determine the relationship between internet addiction with the four (4) main issues in cyber ethics: Privacy, Accuracy, Property, Access (PAPA). A total of 275 respondents were randomly selected regardless of factors such as gender, age, and computer knowledge using paper-based questionnaire. The questionnaire consists of 19 items to test the level of internet addiction and 20 items to gather information on cyber ethic issues. Data was then analyzed using Statistical Package for Social Sciences (SPSS) 24 which uses descriptive statistics (frequency and percentage) to define the level of internet addiction among students and using the Pearson correlation test to determine the relationship between internet addiction and the cyber ethic issues. Results shows that there is a significant difference on internet addiction level among mild, moderate, and severe. A percentage of 13.82% students are in mild level of internet addiction, 76.36% are in moderate level of internet addiction while only 9.82% are in the severe level of internet addiction. Finally, tit was depicted that there was a significant positive relationship between internet addiction and Accuracy, Property and Access whereas there was a negative relationship between internet addiction and Privacy.